"Wielotorowość" rozwoju teorii nauczania i uczenia się literatury a problem poznawczego ujęcia ich historii = The variety of streams in the development of the theories of teaching andlearning literature versus the problem of cognitive formulation of ther history - Boruta, Adam; Jazownik, Leszek (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper includes two "layers" - the metadidactic-literary layer and the methodological one. The first of them is constituted by the formulations connected with the structure of the teaching theory and with the problems of reconstructing the history of literature didactics. The latter is constituted by the discussion of the utalitarian - in so called empirical science - notion of "theory" as a set of complementary conceptions.
Keywords: dydaktyka literatury; nauczanie - teoria; uczenie się - teoria